Autonomic nervous system and hypothalamic-pituitary-adrenal axis response to experimentally induced cold pain in adolescent non-suicidal self-injury: study protocol - Koenig, Julian; Gaber, Lena; Warth, Marco; Kaess, Michael (BMC psychiatry, 2015)
Adolescent non-suicidal self-injury (NSSI) is associated with altered sensitivity to experimentally induced pain. Adolescents engaging in NSSI report greater pain threshold and pain tolerance, as well as lower pain intensity and pain unpleasantness compared to healthy controls. The experience of pain is associated with reactivity of both the autonomic nervous system (ANS) and the hypothalamic-pituitary-adrenal (HPA) axis. However, previous research has not yet systematically addressed differences in the physiological response to experimentally induced pain comparing adolescents with NSSI and age- and sex-matched healthy controls.
Gesehen am 14.07.2020